1997
DOI: 10.1002/(sici)1097-0290(19970720)55:2<455::aid-bit23>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel preparation method for surfactant‐lipase complexes utilizing water in oil emulsions

Abstract: A novel preparation method for surfactantHowever, to take full advantage of the biocatalysis lipase complexes has been developed utilizing water in in an organic medium, it is necessary to modify the oil emulsions. In order to optimize the preparation condienzymes to be soluble in an organic solvent from the tions, we have investigated the effects of several operaviewpoint of reduced diffusional limitations of subtional parameters on the enzymatic activity of the surfacstrates and increase in reaction rates. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In particular, the homogeneous enzymatic reaction in a nonaqueous medium with an enzyme dissolved by means of various methods is more attractive than the heterogeneous reaction using an insoluble enzyme because of the higher catalytic activity. The external surface of the enzyme is converted into a hydrophobic property by chemical modification, such as coating with a surfactant [51,52], modification with an oil-soluble polymer (PEGylation) [53], and encapsulation by a supramolecular assembly (reversed micelle) [54].…”
Section: (Iii) Catalytic Oxidation By the Cytochrome C Extracted In Omentioning
confidence: 99%
“…In particular, the homogeneous enzymatic reaction in a nonaqueous medium with an enzyme dissolved by means of various methods is more attractive than the heterogeneous reaction using an insoluble enzyme because of the higher catalytic activity. The external surface of the enzyme is converted into a hydrophobic property by chemical modification, such as coating with a surfactant [51,52], modification with an oil-soluble polymer (PEGylation) [53], and encapsulation by a supramolecular assembly (reversed micelle) [54].…”
Section: (Iii) Catalytic Oxidation By the Cytochrome C Extracted In Omentioning
confidence: 99%
“…The surfactant−protease complex was formed by the novel preparation method utilizing the water‐in‐oil emulsion, while the surfactant‐coated protease was formed by a conventional preparation method which was first reported by Okahata and Ijiro (1988). The yield of the surfactant−protease complex is theoretically 100% (Okazaki et al, 1997), while those of surfactant‐coated proteases were 22−28%. A lyophilized protease was prepared by the following procedure: protease (10 g/L) was dissolved in 50 mL of phosphate buffer at optimum pH and lyophilized for 24 h. All enzyme preparations except for commercial samples (native proteases) were conducted with the same potassium phosphate buffer solution.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have introduced the new and easy preparation method for surfactant−lipase complexes utilizing water‐in‐oil (W/O) emulsions. It was found that the complexes prepared by the novel method exhibited much higher activity compared with that of native powder lipase in anhydrous isooctane (Okazaki et al, 1997). This novel preparation method can be easily applied to many enzymes because this method does not need a special modifying technique for the enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Under the optimum additive condition (30 mg/ml CTAB), the activity of PPL was about 1.8-fold than that in pure buffer medium. It was well known that lipases displayed a very complex mechanism of action, including the process of ''interfacial activation'' [32][33][34]. Lipases may exist in two different forms.…”
Section: Effect Of Surfactantmentioning
confidence: 99%